Ecological vulnerability assessment of coral islands and reefs in the South China Sea based on remote sensing and reanalysis data - Ma, Yuan; Jiang, Changbo; Li, Shanshan; Liu, Yizhuang; Wen, Xiaofeng; Long, Yuannan; Yuan, Shuai; Kang, Yuantai; Wang, Yongjie; Wu, Ruixuan (Frontiers in Ecology and Evolution, 2023)
Coral reefs are ecosystems that are highly vulnerable to external environmental impacts, including changes associated with ocean acidification and global warming. Assessing the vulnerability of coral reef growth environments over large areas of the sea is a difficult and complex process, as it is influenced by many variables. There are few studies on environmental vulnerability assessment of coral islands and reefs in the South China Sea. It is therefore particularly important to understand the environmental sensitivity of corals and how coral communities respond to changes in climate -related environmental variables. In this study, indicators were selected mainly from natural environmental factors that hinder the development of coral reefs. The sea surface temperature (SST), surface salinity (SSS), wind velocity (WV) and direction, sea level height (SL), ocean currents (OC), and chlo rophyll concentration (Chl) of coral reefs in South China Sea Island were integrated to calculate the coral reef environmental vulnerability region. In a GIS environment, Spatial Principal Component Analysis (SPCA) was used to develop sensitivity models and evaluate the ecological vulnerability of coral reefs.Based on the Environmental vulnerability indicator (EVI) values, the study area was classified as 5 grades of ecological vulnerability: Potential (0.000-0.577) 、Light (0.577-0.780)、Medium (0.780-0.886)、Heavy (0.886-0.993) and Very heavy (0.993-1.131). Sensitivity models identified regional gradients of environmental stress and found that some coral reefs in western Malaysia and southwestern Philippines have higher vulnerability. Meanwhile, the study found that the reefs of Paracel Islands and Macclesfield Bank areas of medium vulnerability. Future use of high-precision data from long time series will allow better estimates of site-specific vulnerability and allow for the precise establishment of marine protected areas so that the ecological diversity of coral reefs can be sustained.